2013
DOI: 10.1102/1470-5206.2013.0009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous peripartum liver haemorrhage presenting as foetal distress

Abstract: We present the case of a 32-year-old woman who presented at 37 weeks' gestation with foetal bradycardia. At caesarean delivery, an intra-abdominal haemorrhage was noted before the uterine incision was made. A subsequent exploratory laparotomy revealed the source of the bleeding to be an extensive ruptured haematoma involving both lobes of the liver. Radiologic investigations revealed the presence of multiple cavernous haemangiomata in the liver. The perioperative management of this patient is described, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another case reported by Tegen et al demonstrated successful management of a ruptured subcapsular hematoma diagnosed intra-operatively with liver packing with hemostatic agents and a drainage catheter placement [ 10 ]. Furthermore, Holst et al reported a diagnosis of a ruptured liver hemangioma that was made postoperatively in a case of a 33-year-old G2P1 when continued hemorrhage was noted [ 11 ]. The patient required an emergent exploratory laparotomy for hematoma evacuation, which revealed a large ruptured subcapsular liver hematoma that was controlled with local surgical hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case reported by Tegen et al demonstrated successful management of a ruptured subcapsular hematoma diagnosed intra-operatively with liver packing with hemostatic agents and a drainage catheter placement [ 10 ]. Furthermore, Holst et al reported a diagnosis of a ruptured liver hemangioma that was made postoperatively in a case of a 33-year-old G2P1 when continued hemorrhage was noted [ 11 ]. The patient required an emergent exploratory laparotomy for hematoma evacuation, which revealed a large ruptured subcapsular liver hematoma that was controlled with local surgical hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was taken to the intensive care unit and received multiple transfusions and a continuous infusion of aprotinin. She remained stable and extubated five days later without suffering from complications after six months follow-up [ 11 ].…”
Section: Discussionmentioning
confidence: 99%